2010
DOI: 10.1371/journal.pone.0014436
|View full text |Cite
|
Sign up to set email alerts
|

No Difference between the Sexes in Fine-Scale Spatial Genetic Structure of Roe Deer

Abstract: BackgroundData on spatial genetic patterns may provide information about the ecological and behavioural mechanisms underlying population structure. Indeed, social organization and dispersal patterns of species may be reflected by the pattern of genetic structure within a population.Methodology/Principal FindingsWe investigated the fine-scale spatial genetic structure of a roe deer (Capreolus capreolus) population in Trois-Fontaines (France) using 12 microsatellite loci. The roe deer is weakly polygynous and hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 38 publications
4
19
0
Order By: Relevance
“…These results are consistent with recent genetic studies, which have reported roe deer to be highly sedentary, exhibiting little or no evidence for sex-biased dispersal (Coulon et al 2006a;Gaillard et al 2008;Bonnot et al 2010). For example, in a study based on the fine-scale genetic structure of a roe deer population in France, anal-yses revealed that the spatial distributions of individuals were not random: adults of both sexes tended to be located spatially close to their relatives (Bonnot et al 2010). Superimposed on a natural tendency for site fidelity in roe deer is an apparent further restriction to movement due to habitat fragmentation.…”
Section: Population Structuresupporting
confidence: 92%
See 2 more Smart Citations
“…These results are consistent with recent genetic studies, which have reported roe deer to be highly sedentary, exhibiting little or no evidence for sex-biased dispersal (Coulon et al 2006a;Gaillard et al 2008;Bonnot et al 2010). For example, in a study based on the fine-scale genetic structure of a roe deer population in France, anal-yses revealed that the spatial distributions of individuals were not random: adults of both sexes tended to be located spatially close to their relatives (Bonnot et al 2010). Superimposed on a natural tendency for site fidelity in roe deer is an apparent further restriction to movement due to habitat fragmentation.…”
Section: Population Structuresupporting
confidence: 92%
“…; Bonnot et al. ). For example, in a study based on the fine‐scale genetic structure of a roe deer population in France, analyses revealed that the spatial distributions of individuals were not random: adults of both sexes tended to be located spatially close to their relatives (Bonnot et al.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Dispersal in mammals is usually biased toward males (reviewed by Lawson Handley and Perrin 2007); however, we did not detect clear evidence of sex-biased dispersal in this study as suggested by the spatial autocorrelation analysis that showed similar patterns in both sexes. Although the lack of sex-biased dispersal in mammals has rarely been observed, it has been reported in several mammals such as the European roe deer (Capreolus capreolus) (Bonnot et al 2010) and the southern water vole (Arvicola sapidus) (Centeno-Cuadros et al 2011). Social and mating systems influence sex bias in mammal dispersal (Lawson Handley and Perrin 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Although the lack of sex‐biased dispersal in mammals has rarely been observed, it has been reported in several mammals such as the European roe deer ( Capreolus capreolus ) (Bonnot et al. ) and the southern water vole ( Arvicola sapidus ) (Centeno‐Cuadros et al. ).…”
Section: Discussionmentioning
confidence: 99%